INTERMITTENT RIVERS OF THE BRAZILIAN NORTHEAST: THE CASE OF ALTO PARAÍBA, BRASIL - da Silva, Janaína Barbosa; Duarte, Simone Mirtes Araújo (Ciência & Trópico, 2017)
A country with continental dimensions such as Brazil has significant environmental diversities throughout its territory. Among these, water resources have unique connotations, from the natural, environmental and social standpoints. The Northeastern region of the country is marked by the presence of temporary rivers, also referred to as intermittent or ephemeral rivers. This condition stems from the characteristic water regime of the Semi-Arid region, which, as a response to the precipitation, establishing a drought period, the riverbeds remain dry for a period of the year. Thus, in the northeastern region, most rivers are intermittent at least in one of their stretches, as is the case with tributaries of the upper course of the Paraíba River. Given their intermittent condition, the beds of these rivers present significant changes over time and space. Thus, this research aimed to identify the uses of the surface along the area of the Alto Paraíba basin, in particular the existence of natural and anthropogenic vegetation; their physiognomies based on the types of densification; surface uses; and areas susceptible to degradation. To do so, we used of geotechnologies (satellite images, Geographic Information Systems, and GPS receiver) in the environmental assessments, while conducting a diagnosis of the high course of the Paraíba River. This research identified the predominance of anthropogenic areas to the detriment of natural vegetation. The less degraded areas were located in the higher altimetric levels, with dense and semi-dense vegetation, while the flat ones, with lower altimetry, are mainly of Exposed Soil, Sparse and Semi-Sparse vegetation. The river courses are the sparsest areas, and the presence of water was insignificant across the area, being restricted to artificial reservoirs. These results enable the scientific, civil and political communities to know the current conditions of this basin, favoring extensive preservation discussions. It was identified that the presence or absence of water is a preponderant factor in the use of the surface.